x + 2 - 5/8 = 2x - 3 + 1/8
Soluções para a tarefa
Respondido por
1
Boa tarde
![x + 2 - \frac{5}{8} = 2x - 3 + \frac{1}{8} x + 2 - \frac{5}{8} = 2x - 3 + \frac{1}{8}](https://tex.z-dn.net/?f=x+%2B+2+-++%5Cfrac%7B5%7D%7B8%7D+%3D+2x+-+3+%2B++%5Cfrac%7B1%7D%7B8%7D+)
mmc = 8
8x + 16 - 5 = 16x - 24 + 1
8x + 11 = 16x - 23
11 + 23 = 16x - 8x
34 = 8x
x =![\frac{34}{8} \frac{34}{8}](https://tex.z-dn.net/?f=+%5Cfrac%7B34%7D%7B8%7D+)
x =
mmc = 8
8x + 16 - 5 = 16x - 24 + 1
8x + 11 = 16x - 23
11 + 23 = 16x - 8x
34 = 8x
x =
x =
Respondido por
1
aí está... espero ter ajudado
Anexos:
![](https://pt-static.z-dn.net/files/db6/0d8b995f09bbe67d5e612f895af70c94.jpg)
Perguntas interessantes
Geografia,
11 meses atrás
Sociologia,
11 meses atrás
História,
11 meses atrás
História,
1 ano atrás
Informática,
1 ano atrás
Matemática,
1 ano atrás
Química,
1 ano atrás